The Effectiveness of Melpredia Prediabetes Self Management Education Based on Android Applications on HbA1c Levels in People with Prediabetes - Amelia Nurul Hakim; Hotma Rumahorbo; Sudirman Sudirman (Universitas Muhammadiyah Malang, 2022)
Introduction: Prediabetes is a condition that will develop into type 2 Diabetes Mellitus (DMT2) within 3-5 years. Glycaemic control is the primary intervention in long-term management, so structured education with appropriate and sustainable media is needed using mobile health technology. Objectives: The development of the "Melpredia" application based on an android application as a media for health promotion and its effect on HbA1c glycaemic control and self-care management. Methods: The Research type was Research and Development (R&D), and model testing using Quasi-experiments with pre-test post-test control group design was carried out for three months from January to April 2021. The purposive sampling technique consisted of 15 intervention groups and 15 control groups. The data were tested using Paired t-test and an independent t-test. The research instrument used by application "Melpredia." Results: The Android-based Melpredia application obtained a percentage of 89% (Fair) and the feasibility test for material aspects with a percentage of 90% (excellent). Using the Melpredia application has the effect of Prediabetes Self-Management Education based on an android application on HbA1c levels of 5.927 ± 0.1831 in people with prediabetes than conventional health promotion (p = 0.001). Conclusions: Application "Melpredia" android based and can effectively improve the HbA1c levels and self-care management of prediabetes in preventing diabetes mellitus by utilizing educational menu, meal planning, physical activity, and reminders use applications. "Melpredia" is more effective than conventional.